SIRPγ-CD47 Interaction Positively Regulates the Activation of Human T Cells in Situation of Chronic Stimulation - Dehmani, Safa; Nerrière-Daguin, Véronique; Néel, Mélanie; Elain-Duret, Nathan; Heslan, Jean-Marie; Belarif, Lyssia; Mary, Caroline; Thepenier, Virginie; Biteau, Kevin; Poirier, Nicolas; Blancho, Gilles; Haspot, Fabienne (Frontiers in Immunology, 2021)
A numerous number of positive and negative signals via various molecules modulate T cell activation. Within the various transmembrane proteins, SIRP is of interest since it is not expressed in rodents. SIRP interaction with CD47 is re-evaluated in this study. Indeed, we show that the anti- SIRP mAb clone LSB2.20 previously used by others as a blocking antibody was mistaken. We reveal that the anti- SIRPclone KWAR23, is a Pan anti-SIRP mAb which efficiently blocks SIRPand SIRPinteractions with CD47. We show that SIRP expression on T cells varies with their differentiation and while being expressed on Tregs, is not implicated in their suppressive functions. SIRPγ spatial reorganization at the immune synapse is independent of its interaction with CD47. In vitro SIRP-CD47 blockade with KWAR23 impairs IFN- secretion by chronically activated T cells. In vivo in a xeno-GvHD model in NSG mice, the SIRPCD47 blockade with the KWAR23 significantly delays the onset of the xeno-GvHD and deeply impairs human chimerism. In conclusion, we have shown that T cell interaction with CD47 is of importance notably in chronic stimulation